Terapi Empati Sebagai Upaya Menurunkan Tindakan Bullying Pada Anak Usia Sekolah di SD N Karanggayam - rahmahwidyaningrum (ABDIMAS Madani, 2022)
Introduction: schools have a function as a formal institution that transfers knowledge and as a second home in creating a new ecosystem for the growth of students' character and competence. A good social environment is a psychological determinant of students that affects learning outcomes. Cases of bullying from year to year are increasing which include: ridicule, exclusion, beating, kicking and pushing. The most severe impact of bullying is depression to suicide attempts. The school environment, family and peers are factors that can influence the emergence of bullying in schools. Several types of programs have been offered to reduce bullying. Objective: To increase students' knowledge about bullying and to instill Islamic values to behave according to morality. Methods: the community service was carried out on 31 May 2022 through a classical lecture method approach for 45 minutes followed by a discussion session. The target audience was 39 students and 2 accompanying class teachers. The follow-up was in the form of a booklet with the theme "Let's Stay Away from Bullying and Love Your Friends" which was handed over to student representatives and the school. Results: the majority of the targets were in the 4th grade of elementary school (20 people/51.28%) with the percentage of male students more than 22 students (56.41%). Characteristics of bullying actions that have been carried out by students of SD N Karanggayam in the form of: hitting (7 students/17.94%), laughing at (23 students/58.97%) and social bullying in the form of isolating or not inviting to play (1 student (2.56%). Conclusion: After the community service activities, students' understanding of bullying increased.